Transcriptome sequencing analysis of the role of miR-499-5p and SOX6 in chicken skeletal myofiber specification - Liu, Yi-Fan; Zhang, Ming; Shan, Yan-Ju; Pang, Li-Chuan; Ji, Gai-Ge; Ju, Xiao-Jun; Tu, Yun-Jie; Shi, Shi-Ying; Bai, Hao; Zou, Jian-Min; Shu, Jing-Ting (Frontiers in Genetics, 2022)
microRNAs (miRNAs) might play critical roles in skeletal myofiber specification. In a previous study, we found that chicken miR-499-5p is specifically expressed in slow muscle and that its potential target gene was SOX6. In this study, we performed RNA sequencing to investigate the effects of SOX6 and miR-499-5p on the modulation and regulation of chicken muscle fiber type and its regulatory mechanism. Expression levels of miR-499-5p and SOX6 demonstrated opposing trends in different skeletal muscles and were associated with muscle fiber type composition. Differential expression analysis revealed that miR-499-5p overexpression led to significant changes in the expression of 297 genes in chicken primary myoblasts (CPMs). Myofiber type-related genes, including MYH7B and CSRP3, showed expression patterns similar to those in slow muscle. According to functional enrichment analysis, differentially expressed genes were mostly associated with muscle development and muscle fiber-related processes. SOX6 was identified as the target gene of miR-499-5p in CPM by using target gene mining and luciferase reporter assays. In this study, SOX6 knockdown resulted in upregulation of the slow myosin genes and downregulation of fast myosin genes. Furthermore, protein interaction network analysis revealed that MYH7B and RUNX2 may be the direct targets of SOX6. These results indicated that chicken miR-499-5p may promote slow muscle fiber formation by repressing SOX6 expression. Our study provides a dataset that can be used as a reference for animal meat quality and human muscle disease studies.